Socialization of Understanding Manual Material Handling and K3 for Manufacturing Industry Workers - Megasari Kurnia; Ilham Bakri; Putri Indah Wardani; Retnari Dian Mudiastuti; Nadzirah Ikasari Syamsul (Faculty of Engineering UNHAS, 2026)
This Community Service Program was conducted at a manufacturing company, PT. Andalan Fluid Sistem, which specializes in hydraulic and pneumatic cylinder services. The main issue faced by the partner company was the uneven level of workers’ knowledge regarding manual material handling techniques that comply with ergonomic and occupational safety and health principles. This program aimed to improve the knowledge of industrial workers in the manufacturing sector regarding Manual Material Handling (MMH) and Occupational Safety and Health (OSH) to support safe and productive work practices. The materials delivered included industrial ergonomics theory, Manual Material Handling (MMH), and Behavior-Based Safety (BBS) to provide workers with an understanding of the importance of proper manual material handling techniques. The program activities consisted of a pre-test, educational sessions, and a post-test involving 12 participants from managerial, production, and occupational safety departments. The analysis results indicated a significant improvement in workers’ understanding after participating in the program. Quantitatively, the post-test scores increased compared to the pre-test scores, with the average score rising from 5.4 in the pre-test to 9.2 in the post-test. Qualitatively, participants demonstrated high enthusiasm and a greater commitment to safe work practices. Overall, the program was effective in enhancing workers’ competence and awareness of ergonomics, while also strengthening the occupational safety and health culture within the manufacturing industry.